2023
DOI: 10.3390/ijerph21010025
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Injustice and Electronic Waste in Ghana: Challenges and Recommendations

Anuli Njoku,
Martin Agbalenyo,
Janaya Laude
et al.

Abstract: Electronic waste (e-waste) or discarded electronic devices that are unwanted, not working, or have reached their end of life pose significant threats to human and environmental health. This is a major concern in Africa, where the majority of e-waste is discarded. In the year 2021, an estimated 57.4 million metric tons of e-waste were generated worldwide. Globally, COVID-19 lockdowns have contributed to increased e-waste generation. Although Africa generates the least of this waste, the continent has been the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Waste in general, especially hazardous waste, may cause harm to humans, animals, plants, and water [10,33,47]. Therefore, it is very important to dispose of it properly [2,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste in general, especially hazardous waste, may cause harm to humans, animals, plants, and water [10,33,47]. Therefore, it is very important to dispose of it properly [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…Based on their review, Sapkota and Pariatamby [32] (p. 83) reported that "households and healthcare facilities usually dispose of contaminated, unused, or expired medicines with municipal waste". There is no doubt that these practices have dire effects on human health and the environment [2,10], in addition to the serious harm that may befall waste collection workers, especially when they do not use personal protective equipment [33]. Therefore, to develop sustainable practices, stakeholders should adopt green business models that consider the environmental, social, and economic dimensions [22].…”
Section: Green Start-up Projects To Collect Unwanted Drugsmentioning
confidence: 99%